Genetic and Environmental Contributions to the Relationship Between Internalizing Disorders and Sick Leave Granted for Mental and Somatic Disorders. (August 2014) - Torvik, Fartein A.; Gjerde, Line C.; Røysamb, Espen; Tambs, Kristian; Kendler, Kenneth S.; Czajkowski, Nikolai O.; Knudsen, Gun P.; Reichborn-Kjennerud, Ted; Ørstavik, Ragnhild E.
<x content-type="archive" xml:space="preserve">Abstract</x> This study investigates the degree to which internalizing disorders (anxiety and mood disorders) are prospectively associated with sick leave granted for mental and somatic disorders, and the extent to which common genetic and environmental risk factors influence these relationships. Data include self-reported symptoms of psychological distress from 7, 598 young adult twins and diagnostic interviews on a subsample of 2, 766 adult twins, subsequently linked to registry data on sick leave. Regression analyses and multivariate twin models were used to investigate the relationship between internalizing disorders and sick leave. Internalizing disorders were associated with sick leave granted for both mental disorders and somatic disorders. The association between internalizing disorders and sick leave granted for mental disorders was influenced by genetic and non-shared environmental factors, while the association between internalizing disorders and sick leave granted for somatic disorders could be explained by common genetic factors alone. Monozygotic twins discordant for internalizing disorders differed significantly in rates of sick leave granted for mental but not somatic disorders. In conclusion, internalizing disorders in young adults predict sick leave granted for both mental and somatic disorders. Environmental risk factors for internalizing disorders seem to influence sick leave granted for mental disorders, but not sick leave granted for somatic disorders.